Comparative Immune- and Stress-Related Transcript Response Induced by Air Exposure and Vibrio anguillarum Bacterin in Rainbow Trout (Oncorhynchus mykiss) and Gilthead Seabream (Sparus aurata) Mucosal Surfaces - Khansari, Ali Reza; Balasch, Joan Carles; Vallejos-Vidal, Eva; Parra, David; Reyes-López, Felipe E.; Tort, Lluís (Frontiers in Immunology, 2018)
Fish have to face various environmental challenges that may compromise the efficacy of the immune response in mucosal surfaces. Since the effect of acute stress on mucosal barriers in fish has still not been fully elucidated, we aimed to compare the short-term mucosal stress and immune transcriptomic responses in a freshwater (rainbow trout, Oncorhynchus mykiss) and a marine fish (gilthead seabream, Sparus aurata) to bacterial immersion (Vibrio anguillarum bacterin vaccine) and air exposure stress in skin, gills and intestine. Air exposure and combined (vaccine+air) stressors exposure were found to be inducers of the cortisol secretion in plasma and skin mucus on both species in a time dependent manner, while V. anguillarum bacterin exposure induced cortisol release in trout skin mucus only. This was coincident with a marked differential increase in transcriptomic patterns of stress and immune related gene expression profiles. Particularly in seabream skin, the expression of cytokines was markedly enhanced, whereas in gills the response was mainly suppressed. In rainbow trout gut both air exposure and vaccine stimulated the transcriptomic response, while in seabream stress and immune responses were mainly induced by air exposure. Therefore, our comparative survey on the transcriptomic mucosal responses demonstrates that skin and gut were generally more reactive in both species. However, the upregulation of immune transcripts was more pronounced in gills and gut of vaccinated trout, whereas seabream appeared to be more stress-prone and less responsive to Vibrio anguillarum bacterin in gills and gut. When fish were subjected to both treatments no definite pattern was observed. Overall, the results indicate that (1) the immune response was not homogeneous among mucosae, (2) it was greatly influenced by the specific traits of each stressor in each surface, and (3) was highly species-specific, probably as a result of the adaptive life story of each species to the microbial load and environmental characteristics of their respective natural habitats.